Cartografias da ficção: a performance da enunciação dos contadores tradicionais de histórias da cidade de Tapiramutá, na Chapada Diamantina-Bahia: um entrecruzamento entre o fantástico e o cotidiano. - Araújo, Nádia Barros (2024)
This thesis has as its investigative object the performance of enunciation by traditional storytellers from the city of Tapiramutá, in Chapada Diamantina, Bahia, Brazil, and the poetics produced by these cultural actors. The aim is to understand why these tellers make the frequent and repeated choice to narrate fictional plots. Likewise, the aim is to map the relationships and links that exist between these social voices, shared and passed on from generation to generation, through the eyes of a collective, highlighting, based on the stories told, manifestations of social life and ways of acting and perceiving the world. Thus, the intertwining of languages (oral, gesture, performative), social, poetic, fictional and everyday voices was evident in these stories, constituting poetic alterities, traits and identity representations in multiple instances, beliefs, values and interests. The research used a qualitative approach, of an ethnographic nature, in an approximate and dialogical perspective between linguistics and literature. The sample was made up of 22 traditional storytellers, and the main results of this investigation point to a repeated choice for the narrative of fantastic plots, configuring the desire of these cultural actors to signify the world that surrounds them, not just in an isolated and individualized way, but, in the polyphony and heterodiscursivity of many other dialogical subjects, in infinite conversations with plots and voices of countless other tellers from whom they inherited this enchanting craft. This trait reflects, in the poetic alterity of Tapiramutá’s people, a collective poetics, framed by moral and ethical principles, covered with fantastic, legendary, mythological, religious and enchanting aspects.